Novel Porphyrin‐Based Hypercrosslinked Polymers as Highly Efficient Electrocatalysts for Oxygen Reduction Reaction. Issue 5 (20th March 2022) - Zhu, Zhaoqi; Cui, Jie; Cao, Xiaoying; Yang, Lijuan; Sun, Hanxue; Liang, Weidong; Li, Jiyan; Li, An
Abstract : The exploration of high‐performance electrocatalysts is significant to improve the sluggish oxygen reduction reaction (ORR) speed in electrochemical systems. Here, the creation of novel non‐precious metal catalysts via knitting hypercrosslinked polymer (TPP‐HCP‐1) based on porphyrin as the building block which contains both mesopore and catalytic sites, is demonstrated. Interestingly, the TPP‐HCP can be converted into a nitrogen‐doped porous carbon skeleton through pyrolyzing the hybrid at 900 °C, which possesses an excellent ORR electrochemical performance in alkaline medium, with a more positive onset potential of 0.96 V (vs reversible hydrogen electrode, the same in the following), half‐wave potential of 0.85 V, and higher diffusion limiting current density of 4.00 mA cm −2 . Moreover, it also exhibits much higher stability, comparable selectivity, and better methanol tolerance than the commercial Pt/C. Making good use of their high ORR activity and easy fabrication makes it possible to use low‐cost FeCl3 as both catalysts for HCP precursors and metal dopant for the porphyrin‐based hypercrosslinked polymer (TPP‐HCP‐1), thus the obtained TPP‐HCP‐1 may offer novel ideation to construct non‐precious metal catalysts for practical electrocatalytic applications. Abstract : The exploitation of high‐efficiency non‐precious metal electrocatalysts toward oxygen reduction reaction is significant for large‐scale commercialization of next‐generation fuel cells. Here, the creation of novel non‐precious metal catalysts via knitting hypercrosslinked polymers (TPP‐HCP‐1) based on porphyrin as a building block is reported. Interestingly, TPP‐HCP‐1 displayed higher limiting current density values, good durability, and superior methanol tolerance the compared with commercial Pt/C catalyst.